2020
DOI: 10.1016/j.ajogmf.2020.100201
|View full text |Cite
|
Sign up to set email alerts
|

Retracted articles in the obstetrics literature: lessons from the past to change the future

Abstract: BACKGROUND: The publication of invalid scientific findings may have profound implications on medical practice. As the incidence of article retractions has increased over the last 2 decades, organizations have formed, including Retraction Watch, to improve the transparency of scientific publishing. At present, the incidence of article retraction in the obstetrics and maternal-fetal medicine literature is unclear. OBJECTIVE: This study aimed to determine the number of retracted articles within the obstetrics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 10 publications
4
30
1
1
Order By: Relevance
“…Retracted publications have been documented and analyzed in a variety of biomedical disciplines, including dentistry [10][11][12], radiation and oncology [13][14][15], mental health [16], emergency medicine [17], obstetrics and gynecology [18,19], and surgery [20,21]. Previous studies show that a greater proportion of drug therapy articles are retracted for reasons of misconduct and fraud compared with other biomedical studies [22].…”
Section: Introductionmentioning
confidence: 99%
“…Retracted publications have been documented and analyzed in a variety of biomedical disciplines, including dentistry [10][11][12], radiation and oncology [13][14][15], mental health [16], emergency medicine [17], obstetrics and gynecology [18,19], and surgery [20,21]. Previous studies show that a greater proportion of drug therapy articles are retracted for reasons of misconduct and fraud compared with other biomedical studies [22].…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, growing concerns regarding the trustworthiness of the scientific evidence that we all take for granted. 2,3 In this issue, Bennett et al 4 have focused on retracted articles in our field and confirmed that there are no safe havens when it comes to scientific fraud. Untrustworthy data come from all study types and all continents.…”
mentioning
confidence: 87%
“…Importantly, scientific fraud is not confined to predatory journals; journals with a high impact factor are not immune either. Bennett et al 4 take comfort in the fact that retractions seem to appear rather quickly with a low median citation rate. However, I would argue that by focusing on retracted articles as an easily visible tip, we may be missing the rest of this iceberg that is threating the very core of EBM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, 129 retracted manuscripts in obstetrics were identified in RetractionWatch 5 and/or PubMed. 6 Others have questioned the validity of some published RCTs in obstetrics using Monte-Carlo analysis, a modeling technique that simulates a large quantity of random trials from a given dataset and can determine the probability that the reported data in an RCT resulted from groups that were appropriately randomized. 7,8 This problem is not just restricted to ob-gyn journals, but is widespread throughout the medical literature, and may not be simple or straightforward to detect.…”
Section: Introductionmentioning
confidence: 99%